2021
DOI: 10.3390/nano11113071
|View full text |Cite
|
Sign up to set email alerts
|

Solar Light Photoactive Floating Polyaniline/TiO2 Composites for Water Remediation

Abstract: In the present study, the development of innovative polyurethane-polyaniline/TiO2 modified floating materials applied in the sorption and photodegradation of rhodamine B from water matrix under solar light irradiation is reported. All the materials were fabricated with inexpensive and easy approaches and were properly characterized. The effect of the kind of polyaniline (PANI) dopant on the materials’ behavior was investigated, as well as the role of the conducting polymer in the pollutant abatement on the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…The test carried out under light irradiation (both UVA and LED) led to similar results ( Figures S7 and S8 ), confirming that, in photocatalytic processes, pristine PANI does not act as a photocatalyst, but as a photosensitizer [ 81 ].…”
Section: Resultsmentioning
confidence: 52%
“…The test carried out under light irradiation (both UVA and LED) led to similar results ( Figures S7 and S8 ), confirming that, in photocatalytic processes, pristine PANI does not act as a photocatalyst, but as a photosensitizer [ 81 ].…”
Section: Resultsmentioning
confidence: 52%
“…Numerous studies have shown that the primary degradation pathways of RhB involve N -de-ethylation, destruction of the dye's chromophore structure, and ring opening. 39–41 In Fig. 6a, we present the possible pathways of RhB degradation.…”
Section: Resultsmentioning
confidence: 99%
“…† Numerous studies have shown that the primary degradation pathways of RhB involve N-de-ethylation, destruction of the dye's chromophore structure, and ring opening. [39][40][41] In Fig. 6a 42,43 Then the intermediates with m/z value of 314 may occur de-amination, leading to the generation of intermediates with m/z values of 165, 278 and 202.…”
Section: Degradation Of Rhb In Bess Based Bio-electro-fenton Systemmentioning
confidence: 99%
“…Preparing PANI-semiconductor composites has drawn significant attention because of their particular electron and hole-transporting properties, simplicity of synthesis, and chemical stability [ 6 , 32 , 33 , 34 , 35 ]. Although the effect of PANI coating on traditional semiconductors, mainly TiO 2 and ZnO, has been extensively investigated, only a few studies have been dedicated to the photocatalytic properties of PANI/Bi 2 O 3 composites.…”
Section: Introductionmentioning
confidence: 99%